Dialek Daerah pada Percakapan Bahasa Arab Santri di Pesantren: Studi Kasus Pada Pesantren Pendidikan Islam Darul Abrar Bone - Ahmad Munawwir; Muhammad Ihsan; Amran AR; Moh. Sholeh Afyuddin (Shaut al Arabiyyah, 2023)
This study aims to determine the absorption process of regional dialects in the Arabic conversation of class VIII students at KMI PPI Darul Abrar Bone. This type of research is descriptive qualitative with a sociological approach. The results showed that the absorption of regional dialects in the Arabic conversations of class VIII students at KMI PPI Darul Abrar occurred due to environmental factors that still lingered and influenced them, spontaneous factors the effect of the lack of Arabic vocabulary they mastered, and the use of code mixing between Arabic and regional dialects. they. This absorption has an impact on the inability of students to understand language differences well, and their low mastery of Arabic vocabulary. The expected solution is to get used to using good and correct language, using various learning techniques, and applying the audiolingual method to the learning process. The implication of this research is the presence of awareness among teachers that the process of learning Arabic has not been maximized so far, so it is hoped that the solutions offered can be realized optimally